Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.3171/jns.1991.74.1.0081
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe intraventricular hemorrhage by intraventricular infusion of urokinase

Abstract: Six patients with severe intraventricular hemorrhage were treated with direct intraventricular infusion of urokinase. In each case, hemorrhage extended into all ventricular chambers, and a cast formation and expansion of the third and fourth ventricles were found. Immediately after the therapy was started (within 7 days from onset of symptoms), reduction of intraventricular hematoma volume was observed on computerized tomography. On average, both the third and fourth ventricles became clear on the third day af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(90 citation statements)
references
References 6 publications
2
86
0
2
Order By: Relevance
“…This feature of the protocol for UK administration was based on previous findings. 9 In our cohort, clearance of the third ventricle occurred sooner in patients who received UK, and clearance of the third ventricle portended better outcome. This suggests that relief of third ventricular obstruction may be the key observation to guide successful treatment of UK therapy of IVH, and perhaps clearance of third ventricular hemorrhage should be the end point of treatment.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This feature of the protocol for UK administration was based on previous findings. 9 In our cohort, clearance of the third ventricle occurred sooner in patients who received UK, and clearance of the third ventricle portended better outcome. This suggests that relief of third ventricular obstruction may be the key observation to guide successful treatment of UK therapy of IVH, and perhaps clearance of third ventricular hemorrhage should be the end point of treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Other series 9,12,[15][16][17][18] have reported a combined total of 59 patients given intraventricular thrombolytics for spontaneous IVH from either aneurysmal or presumed parenchymal rupture; of these, 17 received UK. 9,12,15 None of these series looked at the same outcome measures we used (eg, LOS), nor did any have a sizable contemporaneous cohort managed without adjunctive thrombolytics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The JCS is widely used for the assessment of impaired consciousness in patients with SAH in Japan. 2,12,14,25,32 Although the JCS cannot assess neurological impairment other than diminished consciousness, the JCS score on admission had the greatest impact on the outcomes of patients with SAH. 9 In addition, JCS scores have been reported to correlate with stroke outcomes.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…What is not clear from the literature, however, is whether such treatment results in an improved neurological outcome of the survivors. Shen et al, 43 Akdemir et al, 1 and Todo et al 46 reported good recovery with or without moderate disability in 50%-83% of the patients who received this treatment. However, 1 cohort study found that a larger proportion of the survivors remained in a vegetative state (31.8% treatment group vs 11.1% control group).…”
mentioning
confidence: 99%